2013
DOI: 10.1111/rda.12244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short‐Term Scrotal Hyperthermia on Spermatological Parameters, Testicular Blood Flow and Gonadal Tissue in Dogs

Abstract: The objective was to assess the effect of a short-term scrotal hyperthermia in dogs on quantitative and qualitative ejaculate parameters, testicular blood flow and testicular and epididymal histology. After a control period, the scrotum of seven normospermic adult beagle dogs was insulated with a self-made suspensory for 48 h. Nine weeks later, two animals were castrated, while in five animals, scrotal hyperthermia was repeated. Dogs were castrated either 10 or 40 days thereafter. In each phase of scrotal insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
2
26
1
Order By: Relevance
“…Our results showed that the local testicular heating caused a significant increase in the TUNEL‐positive cell numbers of round and elongated spermatids. Our results agree with prior reports (Lue et al., ; Yamamoto et al., ; Oldereid et al., ; Hikim et al., ; Zhang et al., , ; Merico et al., ; Jia et al., ; Paul et al., ; Kanter et al., ; Liang et al., ; Henning et al., ), in which heat stress resulted in the apoptosis of germ cells. But a little different from the report by Lue et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that the local testicular heating caused a significant increase in the TUNEL‐positive cell numbers of round and elongated spermatids. Our results agree with prior reports (Lue et al., ; Yamamoto et al., ; Oldereid et al., ; Hikim et al., ; Zhang et al., , ; Merico et al., ; Jia et al., ; Paul et al., ; Kanter et al., ; Liang et al., ; Henning et al., ), in which heat stress resulted in the apoptosis of germ cells. But a little different from the report by Lue et al.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a self‐made thermo‐controlled 42°C blanket was used in the local testicular heating group. Recently, several studies in a few animals suggested that testes exposed to above body temperature (40–43°C) cause apoptosis in germ cells, including mice (Merico et al., ; Paul, Teng, & Saunders, ; Liang, Dong, Zhao, & Li, ), rats (Yamamoto et al., ; Hikim et al., ; Jia et al., ), dogs (Henning et al., ) and monkeys (Zhang et al., , ). Several studies also confirmed that exposing testes to above body temperature affects normal spermatogenesis, sperm fertility and male fertility (Gnay et al., ; Ikeda et al., ; Gau et al., ; Li et al., ; Guo et al., ; Salces‐Ortiz et al., ; Xun et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…While several theories have been proposed to explain the deleterious effects of varicocele on testicular function, testicular hyperthermia is perhaps the most commonly accepted one. It has long been observed that minor changes in testicular temperature can affect spermatogenesis (52) as many of the enzymes responsible for DNA synthesis in the testis are temperature dependent (53), mainly favoring temperatures lower than 98.2±0.72 °F (normal body temperature). The anatomic position of the testis in the scrotal sac together with the countercurrent cooling mechanism provided by the pampiniform plexus of veins are responsible regulating testicular temperature (54).…”
Section: Indications For Sdf Testingmentioning
confidence: 99%
“…Scrotal heating can cause temporary or permanent infertility, such as occupationally (bakers, welders, foundry workers) or through submerging in a hot water bath (Mieusset & Bujan, 1995;Thonneau, Bujan, Multigner, & Mieusset, 1998). Several studies have also illustrated that the elevation of testicular temperature affects the spermatogenesis and semen quality in most mammals, including mouse (Paul et al, 2009), dogs (Henning et al, 2014), monkeys (Zhang et al, 2004) and bulls as well (Ax, Gilbert, & Shook, 1987). Furthermore, Cai et al (2011) demonstrated that scrotal heating usually affects spermatogenesis by altering the expression of tight junctions (TJs) molecules.…”
Section: Introductionmentioning
confidence: 99%